Promoting cooperation: the distribution of reward and punishment power - Nosenzo, Daniele; Sefton, Martin (Oxford University Press, 2014)
Recent work in experimental economics on the effectiveness of rewards and punishments for promoting cooperation mainly examines decentralized incentive systems where all group members can reward and/or punish one another. Many self-organizing groups and societies, however, concentrate the power to reward or punish in the hands of a subset of group members (‘central monitors’). We review the literature on the relative merits of punishment and rewards when the distribution of incentive power is diffused across group members, as in most of the extant literature, and compare this with more recent work and new evidence showing how concentrating reward/punishment power in one group member affects cooperation.